Music and death funeral music, memory and re-evaluating life - Marx, Wolfgang 1967- (Boydell Press, 2023)
Music gives specific meanings to our lives, but also to how we experience death; it forms a central part of death rituals, consoles survivors, and celebrates the deceased.0Music & Death investigates different musical engagements with death. Its eleven essays examine a broad range of genres, styles and periods of Western music from the Middle Ages until the present day. This volume brings a variety of methodological approaches to bear on a broad, but non-exhaustive, range of music. These include musical rituals and intercessions on behalf of the departed. Chapters also focus on musicians' reactions to death, their ways of engaging with grief, anger and acceptance, and the public's reaction to the death of musicians. 0The genres covered include requiem settings, operas and ballets, arts songs, songs by Leonard Cohen and the B-52s, and instrumental music. There are also broader reflections regarding the psychological links between creative musical practice and the overcoming of grief, music's central role in shaping a specific lifestyle (of psychobillies) and the supposed universalism of Western art music (as exemplified by Brahms). 0The volume adds many new facets to the area of death studies, highlighting different aspects of "musical thanatology". It will appeal to those interested in the intersections between western music and theology, as well as scholars of anthropology and cultural studies
Keywords: Geschichte; Bestattungsmusik; Tod; Requiem-Vertonung; Tod -- Motiv; Verlust -- Motiv; Erinnerung -- Motiv; Musik; Funeral music / History and criticism; Death in music; Funeral music; Criticism, interpretation, etc; Aufsatzsammlung